2005
DOI: 10.1111/j.1365-2184.2005.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

The hTERT‐protein and Ki‐67 labelling index in recurrent and non‐recurrent meningiomas

Abstract: Meningiomas are considered as benign neoplasms affecting the coverings of the central nervous system and compromise approximately 20% of all intracranial tumours. However, a number of these tumours recur even after total resection. The aim of this study is to evaluate the prognostic significance for recurrence of the human telomerase catalytic subunit (hTERT) in the cells of meningiomas. The expression of hTERT-protein can be evaluated by immunohistochemical staining using a monoclonal antibody against hTERT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 20 publications
0
23
0
5
Order By: Relevance
“…Telomere length is maintained by telomerase activity and can be influenced in different ways and by various factors (26). From literature it is clear that telomerase activity can be regarded as a prognostic marker for malignancy (12,13,16). In contrast to malignant intracranial tumours, benign meningiomas seldom express telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomere length is maintained by telomerase activity and can be influenced in different ways and by various factors (26). From literature it is clear that telomerase activity can be regarded as a prognostic marker for malignancy (12,13,16). In contrast to malignant intracranial tumours, benign meningiomas seldom express telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some results have already been published on telomerase and telomeres in intracranial tumours (12)(13)(14), showing a correlation between telomerase activity and histopathological grading. It has been reported that hTERT rather than telomerase activity could be used as a prognostic marker for progression and potential recurrence (15)(16)(17). Moreover, hTERT could be considered as an early signal towards indefinite life span (18).…”
Section: Introductionmentioning
confidence: 99%
“…25 In contrast to this finding, Maes et al found Ki-67 to be a good marker of the cell proliferation status of the tumors but found no correlation with recurrence. 9 They observed that human telomerase catalytic subunit (hTERT) alone seemed to be a potential predictor of recurrence. In our study, the statistical results showed that the Ki-67 labeling index was highly correlated with meningioma grading but not with brain invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Ki67 expression corresponds to WHO classification and tends to be correlated with the biologic behavior of these different groups (i.e., benign, atypical, and malignant) does not indicate whether the tumor has a tendency to recur. 24 In canine and feline meningioma, the finding of MMP expression calls for further investigations into the role played by MMPs, perhaps in relation to a revised morphologic malignancy grading and to the recurrence of intracranial or spinal meningioma, whether benign or malignant, along with other factors influencing tumor invasion into the brain or spinal cord and its recurrence, such as location, extent of surgery, intraoperative findings, radiographic aspects, age of the patient, edema, cytokine production, and possibly the chromosomal alteration.…”
Section: Discussionmentioning
confidence: 99%